Prevention Measure and Reason of Segment Plate Generates Cracks in the Process of Hot Strip Coiling Transmission - Zhao Shengkun; Li Yong (Jixie chuandong)
In order to analyze the reason of the hot- rolled segment plate generates cracks in long- term use,combining with the actual situation and using ANSYS,the thermal coupling model is established,and the temperature field and stress field in the using process are analyzed. The results show the main reason of the segment plate causing cracking is the temperature field and the inhomogeneity of the thermal stress field,the local regional focus stress and the thermal fatigue during the coiling process,and the methods and measures of improving and preventing the cracks are put forward.